New Pathophysiological Considerations on Cerebral Aneurysms - Jung, Keun-Hwa (Neurointervention, 2018)
Cerebral aneurysm is a common cerebrovascular disease that is sometimes complicated by rupture or an enlarged mass. We are now aggressively evaluating and managing unruptured cerebral aneurysms based on a significant concern for the high morbidity and mortality related to its associated complications. However, the actual rupture rate is very low and the diagnostic and treatment modalities are expensive and invasive, which may lead to unnecessary costs and potential medical complications. This disproportionate situation is related to a poor understanding of the natural course and pathophysiology of cerebral aneurysms. In consideration of the concept that not all cerebral aneurysms must be removed, we need to examine their course and progression more accurately. Cerebral aneurysms may follow a variety of pathophysiological scenarios over their lifetime, from formation to growth and rupture. The disease course and the final outcome can differ depending on the timing and intensity of the pathological signals acting on the cerebral vessel wall. We should delineate a method of predicting the stability and risk of rupture of the lesion based on a comprehensive knowledge of the vessel wall integrity. This review deals with the basic knowledge and advanced concepts underlying the pathophysiology of cerebral aneurysms.